Conversion of monosaccharides into levulinic acid/esters: impacts of metal sulfate addition and the reaction medium. Issue 11 (31st August 2019) - Sun, Kai; Zhang, Lijun; Shao, Yuewen; Li, Qingyin; Fan, Huailin; Gao, Guanggang; Zhang, Shu; Liu, Qing; Wang, Yi; Hu, Xun
Abstract: BACKGROUND: Inorganic salts could be used as catalysts for the effective conversion of sugars. In this study, the impacts of various metal sulfates (Na2 SO4, K2 SO4, MnSO4, CoSO4, NiSO4, ZnSO4, CuSO4, Fe2 (SO4 )3, La2 (SO4 )3 and Ce(SO4 )2 ) on the conversion of glucose/fructose to levulinic acid in varied reaction media were evaluated. RESULTS: The sulfates strongly chelated with the sugars, preventing their dehydration reactions in the presence of sulfuric acid and leading to polymerization of the sugars. The sulfates themselves showed varied activity and selectivity for the conversion of the sugars to levulinic acid/esters or 5‐hydroxymethylfurfural (HMF), depending on the coordination with the reaction medium. K2 SO4 or Na2 SO4 could catalyze the production of HMF from glucose/fructose in water, while in DMSO the yield of HMF was substantially higher. In THF, nevertheless, almost no HMF was formed, while other sulfates such as NiSO4 in THF could effectively catalyze the conversion of fructose to HMF. In alcohols, Fe2 (SO4 )3 was the most effective sulfate for the conversion of the sugars to levulinic acid/esters, and the alcohols could effectively suppress the polymerization of the sugars. CONCLUSION: The distinct catalytic performances of the sulfates in the varied reaction media originated from their different coordination or chelation with the sugars and the reaction medium. © 2019 Society of Chemical Industry